Performance of Clay Wood Cook Stove: An Analysis of Cost and Fuel Savings - Kuhe, A.; Iortyer, H. A.; Iortsor, A. (Journal of Technology Innovations in Renewable Energy, 2014)
The assessment of cooking energy cost and efficiency of improved woodfuel clay cookstoves in Nigeria have been considered in this study. Two improved wood burning clay cookstove models were compared to the 3-stone fire stove using the water boiling test and controlled cooking test. The following parameters: specific fuel consumption (SFC), thermal efficiency, ebulution time and cooking energy cost were considere as key indicators for comparison. The results show that the fire power for the cold starts phases were 7.72KW, 8.59KW and 9.78KW for the stove with grate, modified stove without grate and the 3-stone open fire (TFS) respectively. The thermal efficiencies ranges between 19-35%, 13.8-26.8% and 11.7-22.8% for the cold start, hot start and simmer phases for mud stove with grate (MSWG), mud stove no grate (MSNG) and three stone open fire (TFS) respectively. MSWG, showed the highest savings potential on wood fuel consumption with the lowest total wood cost of N127.80 and sfc of 1.632Kg of fuel/kg of food cooked. While MSNG and TFS, have a total wood fuel cost and SFC of N207.70 , N269.20, and 2.141, 1.632kg of fuel/kg of food cooked respectively.